Afetividade na relação professor aluno : uma pesquisa bibliográfica exploratória - Alexandre Britto Pereira (2017)
The student teacher relationship is extremely permeated by the issue of affectivity. Historically, the theme of affectivity has been in a secondary position before the primacy of reason, but in recent times has gained great importance in the discussions on education. This bibliographic research aimed to compile and organize studies related to affectivity, specifically in the context of the student teacher relationship. The work sought to debate critically about the theme of affectivity in the context of educational practice. The method chosen was the bibliographic research, with the choice of descriptors related to "affectivity" and "student teacher relationship". The study was carried out in the VHL-PSI Virtual Health Library of Psychology database, encompassing works that deal directly with the theme. The final sample consisted of 56 documents published between 1992 and 2016. The documents selected were analyzed through content analysis in parallel to a bibliometric organization in order to understand how the researchers have dealt with the subject in question. Three categories of analysis were constructed: a) documents that dealt with affectivity; B) documents that focused on the question of the student teacher relationship and c) documents that brought the interface of affectivity in the student teacher relationship. The results show that the affectivity in the student teacher relationship presents direct relationships with the quality of the learning teaching process; that the quality of teacher mediation can produce positive or negative affects and that affectivity cannot be thought isolated from cognition, among others. It is hoped that this exploratory study may help future researchers interested in articulating the theme of affectivity in the educational context, especially in the issue of interpersonal relations between students and teachers.